"Child marriage" in context: exploring local attitudes towards early marriage in rural Tanzania. Issue 1 (1st January 2019) - Schaffnit, Susan B.; Urassa, Mark; Lawson, David W.
Abstract: A global campaign to end "child marriage" has emerged over the last decade as part of growing international commitments to address gender inequities and improve female wellbeing. Campaigns typically assert that young brides have negligible autonomy in the marriage process and that marrying under 18 years has resolutely negative impacts on wellbeing. Yet, surprisingly few studies explore local attitudes towards marriage and its timing within contexts where early marriage is most common. As such our understanding of motivations and potential conflicts of interest leading female adolescents into marriage remain poorly informed by viewpoints of people purportedly at risk. We present an exploratory study of attitudes to early marriage in northwestern Tanzania where marriage before or shortly after 18 years is normative. We use focus group discussions, complimented by a survey of 993 women, to investigate local views on marriage. We explore (i) why people marry, (ii) when marriage is deemed appropriate, and (iii) who guides the marriage process. Contrary to dominant narratives in the end child marriage movement, we find that women are frequently active rather than passive in the selection of when and who to marry. Furthermore, marriage is widely viewed as instrumental in acquiring social status within one's local community. Our conclusions illuminate why rates of early marriage remain high despite potential negative wellbeing consequences and increasingly restrictive laws. We discuss our results in relation to related qualitative studies in other cultural contexts and consider the policy implications for current efforts to limit early marriage in Tanzania and beyond.